Stability analysis of the fractional-order prey-predator model with infection. (2nd November 2021) - Ramesh, Perumal; Sambath, Muniyagounder; Mohd, Mohd Hafiz; Balachandran, Krishnan
ABSTRACT: In this paper, we propose a fractional-order prey-predator model with infection on both populations. First, we prove some important results such as existence, uniqueness, non-negativity and boundedness of the solutions of the fractional-order dynamical system. Next, we discuss the local stability and global stability of the fractional-order prey-predator model. Numerical simulations are presented with several examples.